2017
DOI: 10.1165/rcmb.2016-0080oc
|View full text |Cite|
|
Sign up to set email alerts
|

Hypoxia Modulates Epithelial Permeability via Regulation of Vascular Endothelial Growth Factor in Airway Epithelia

Abstract: Hypoxia resulting from occlusion of the sinus ostium is known to be one of the major pathogenic mechanisms of sinusitis. Hypoxia-inducible factor (HIF)-1 is a widely known transcription factor that induces the cellular response to hypoxic conditions and activates the transcription of several genes, including vascular endothelial growth factor (VEGF). We hypothesized that induced permeability caused by hypoxia is a major pathophysiologic mechanism of upper airway diseases, such as sinusitis. The aim of this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 43 publications
2
27
0
1
Order By: Relevance
“…Our findings are consistent with results of experimental studies reporting vascular hyperpermeability, hypercoagulability, and unbalance of the steady endovascular environment in response to chronic intermittent hypoxia 46,47 and impaired sleep architecture 48 . Potential physiological pathways may include oxidative stress, inflammation, and sympathetic activation 4951 .…”
Section: Discussionsupporting
confidence: 92%
“…Our findings are consistent with results of experimental studies reporting vascular hyperpermeability, hypercoagulability, and unbalance of the steady endovascular environment in response to chronic intermittent hypoxia 46,47 and impaired sleep architecture 48 . Potential physiological pathways may include oxidative stress, inflammation, and sympathetic activation 4951 .…”
Section: Discussionsupporting
confidence: 92%
“…[ 1 , 2 ]. Both the inflammatory process and tumor growth are accompanied by tissue hypoxia, which leads to the formation of new blood vessels under the influence of the vascular endothelial growth factor (VEGF), which is secreted by epithelial cells in conditions of hypoxia [ 3 , 4 ]. The expression level of αvβ3-integrin in endothelial cells is known to be significantly increased in tumor vessels [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…AMP = adenosine monophosphate; HIF = hypoxia-inducible factor; IL = interleukin. findings, 10,11,17 we observed that the major hypoxia-related gene, HIF1A, was upregulated in the sinonasal epithelial tissue from CRSwNP patients compared to control subjects. However, to the best of our knowledge, this is the first report of expression of all known HIFα (HIF1A, EPAS1, HIF3A) and HIFβ (ARNT, ARNT2) genes.…”
Section: Discussionmentioning
confidence: 65%
“…Hypoxia can develop in chronic airway diseases such as sinusitis and asthma due to alterations in microvascular structures and increased metabolism. 9 Published literature demonstrates local activation of the hypoxia signaling pathway with effects such as mucus hypersecretion, 10 increased vascular permeability through VEGF expression, 11 and reduced expression of junction proteins. 12 Other studies have demonstrated an impact of hypoxia on immune cells.…”
Section: Hypoxia-related Genes In Human Sinonasal Epitheliummentioning
confidence: 99%